Characteristics and duties of clinical research nurses: a scoping review - Xing, Ying; Wang, Xinxin; Zhang, Chengrui; Yuan, Weian; Chen, Xinlin; Luan, Wei (Frontiers in Medicine, 2024)
Introduction The characteristics and duties of clinical research nurses (CRNs) are constantly developing and changing with the progress of medical technology and increasing needs in patient care. With the continuous deepening and standardization of clinical trials, the importance and status of CRNs during the whole process of clinical trials are also increasingly valued. Methods A scoping review of studies related to the characteristics and duties of CRNs was conducted to clarify relevant roles and concepts. An electronic search was conducted on three English databases (PubMed, Web of Science, Embase) and two Chinese databases (CNKI and Wanfang database) in December 2023. Two authors independently screened the literature, extracted information from the included literature, and summarized and reported the findings. Results A total of 26 articles published between 1991 and 2023 were analyzed, and four characteristics of CRNs were identified as participants and managers of clinical trials, caregivers and protectors of subjects, coordinators of research teams, and educators. Basic knowledge, skills and literacy, communication and coordination ability, and advanced research ability are the competencies required for CRNs. Conclusion Further studies should focus on the importance of various characteristics of CRNs, so as to improve the quality of clinical trials and promote clinical evidence-based practice.